Dual‐Pore Mesoporous Carbon@Silica Composite Core–Shell Nanospheres for Multidrug Delivery1. Issue 21 (24th April 2014) - Fang, Yin; Zheng, Gengfeng; Yang, Jianping; Tang, Haosha; Zhang, Yafeng; Kong, Biao; Lv, Yingying; Xu, Congjian; Asiri, Abdullah M.; Zi, Jian; Zhang, Fan; Zhao, Dongyuan
Abstract Monodispersed mesoporous phenolic polymer nanospheres with uniform diameters were prepared and used as the core for the further growth of core–shell mesoporous nanorattles. The hierarchical mesoporous nanospheres have a uniform diameter of 200 nm and dual‐ordered mesopores of 3.1 and 5.8 nm. The hierarchical mesostructure and amphiphilicity of the hydrophobic carbon cores and hydrophilic silica shells lead to distinct benefits in multidrug combination therapy with cisplatin and paclitaxel for the treatment of human ovarian cancer, even drug‐resistant strains.